Pembelajaran Matematika SD Berbasis Eco-Friendly Unplugged Coding Terintegrasi AI untuk Problem-Solving dan Computational Thinking - Sri Handayani; Fider Lumbanbatu; Nurhalimah Nurhalimah (Jurnal Minfo Polgan, 2026)
Mathematics learning in elementary schools still faces challenges in simultaneously developing students' problem-solving and computational thinking skills, especially in schools with limited digital devices. This study aims to analyze the effect of elementary school mathematics learning based on eco-friendly unplugged coding integrated with Artificial Intelligence on students' problem-solving and computational thinking. The study used a quantitative approach with an explanatory survey design. Data were collected through questionnaires from 120 public elementary school students in Lubuk Pakam, then analyzed using Partial Least Squares-Structural Equation Modeling with SmartPLS software. The evaluation model included testing convergent validity, discriminant validity, construct reliability, coefficient of determination, and hypothesis testing through bootstrapping. The results showed that elementary school mathematics learning had a positive and significant effect on computational thinking with a path coefficient of 0.649, a t-statistic of 11.630, and a P value of 0.000. A positive and significant effect was also found on problem-solving, with a path coefficient of 0.623, a t-statistic of 10.527, and a P value of 0.000. These findings indicate that the integration of unplugged coding activities, an environmentally friendly context, and AI support can encourage problem decomposition, pattern recognition, algorithm development, debugging, and systematic mathematical problem solving. The research implications confirm that this model can be an innovative and inclusive learning alternative for elementary schools. Further research is recommended using experimental designs, control groups, larger samples, and testing the contribution of each learning component separately.